How EFL Teachers Engage Students: A Multimodal Analysis of Pedagogic Discourse During Classroom Lead-Ins - Qin, Yongli; Wang, Ping (Frontiers in Psychology, 2021)
Classroom lead-in is the initial stage for motivating students to become engaged in class interaction. However, little research, to our knowledge, has analyzed the role of teachers’ multimodal competence reflected through their multimodal pedagogic discourse in the realization of the ultimate goals of classroom lead-ins. Based on the data collected from a teaching contest in China, this paper explores how two winner teachers utilize their multimodal ensembles of communicative modes to engage students during classroom lead-ins. The analysis shows that the higher-level action of lead-in is constructed by different communicative modes and they are orchestrated into multimodal ensembles for the specific function of each move of lead-in. The findings indicate excellent EFL teachers’ high multimodal competence plays a decisive role in performing classroom lead-ins and different lead-ins strategies influence the different orchestration of communicative modes. In the process of constructing multimodal pedagogic discourse, teachers build up their professional image and display their personal charm as well. Future research for multimodal discourse analysis and pedagogic research is suggested in the paper.